Flights-to-control: Time variation in the value of a vote - Docherty, Paul; Easton, Steve; Pinder, Sean (Journal of Corporate Finance, 2021)
Dual-class shares often violate the ‘one share-one vote’ principle, thereby creating the potential for agency problems. We develop a model of time-variation in the pricing of these agency problems, as reflected by the voting premium. A key implication of this model is that insiders face a trade-off between the private benefits of control and the value of their cash-flow claims on the firm, resulting in a negative relationship between the voting premium and the expected present value of firm cash flows. As predicted by this model, we report empirical evidence consistent with ‘flights-to-control’, where the voting premium increases substantially during financial crises and when negative earnings surprises are announced. These relationships are accentuated for firms where agency problems might be expected to be more pronounced. The average voting premium is also shown to decrease around events that reduce the ability for insiders to extract private benefits of control.